1996
DOI: 10.1074/jbc.271.31.18789
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Trp-284, Val-296, and Val-297 of the Human δ-Opioid Receptor in Binding of δ-Selective Ligands

Abstract: Given the high homology in amino acid sequence between the ␦-opioid receptor and the two other types ( and ), distinct residues in this receptor may confer its selectivity to some ligands. In order to identify molecular determinants in the human ␦ receptor responsible for the selectivity of ␦-selective ligands, two different ␦/ chimeras were constructed. In the first one, the ␦ sequence from the top of transmembrane 5 to the C terminus was replaced by the equivalent sequence, and in the second one, 13 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 22 publications
8
86
0
Order By: Relevance
“…This protein binds nonselective opioid ligands but is devoid of affinity for ␦-selective ligands. Our results are in agreement with results from previous studies using /␦ or ␦/ chimeric receptors that have shown that ␦-selective ligands interact mainly with the region containing the sixth transmembrane domain and the third extracellular loop of the ␦-opioid receptor (35)(36)(37)(38)(39)(40)50). In this study, we have delimited this region to 10 amino acids that are located between arginine residue at position 291 and leucine residue at position 300.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This protein binds nonselective opioid ligands but is devoid of affinity for ␦-selective ligands. Our results are in agreement with results from previous studies using /␦ or ␦/ chimeric receptors that have shown that ␦-selective ligands interact mainly with the region containing the sixth transmembrane domain and the third extracellular loop of the ␦-opioid receptor (35)(36)(37)(38)(39)(40)50). In this study, we have delimited this region to 10 amino acids that are located between arginine residue at position 291 and leucine residue at position 300.…”
Section: Discussionsupporting
confidence: 82%
“…A mutant of hDOR with an alanine residue at position 291 instead of an arginine binds ␦-selective ligand DPDPE and SNC-80 with wild-type affinity suggesting that arginine 291 (␦ residue) is not critical for the binding of ␦-selective ligand (35). However, the adjacent residue at position 292 is also an arginine which may compensate for the substitution at position 291.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the TM7 may start at different positions in different GPCRs. The finding that Val7.31(296), Val7.32(297), and Leu7.35(300) are crucial in selectivity of the δOR ligand binding (57,58) is consistent with these residues being part of the binding pocket. (4,59).…”
Section: Tm7 May Be Longer In δOr Than In κOrmentioning
confidence: 61%